Towards a unifying pan-arctic perspective: A conceptual modelling toolkit - Wassmann, P.; Carmack, E.C.; Bluhm, B.A.; Duarte, C.M.; Berge, J.; Brown, K.; Grebmeier, J.M.; Holding, J.; Kosobokova, K.; Kwok, R.; Matrai, P.; Agusti, S.; et al. (Progress in Oceanography, 2020)
International audience